2021
DOI: 10.1002/pan3.10199
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing artificial intelligence technology and social media data to support Cultural Ecosystem Service assessments

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 90 publications
0
29
0
1
Order By: Relevance
“…In an ES context, social media provides a rich new source of data to capture the cultural contributions of ecosystems to human well-being but its use is rarely validated 46 . In the ES community, deep learning applications also remain limited and those that do exist tend to limit their analysis to using the objects detected in images as proxies for cultural ES 25 , 36 , 50 . We have demonstrated that deep learning-based variables which consider the overall semantic meaning of an image can accurately capture the aesthetic quality of the British landscape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an ES context, social media provides a rich new source of data to capture the cultural contributions of ecosystems to human well-being but its use is rarely validated 46 . In the ES community, deep learning applications also remain limited and those that do exist tend to limit their analysis to using the objects detected in images as proxies for cultural ES 25 , 36 , 50 . We have demonstrated that deep learning-based variables which consider the overall semantic meaning of an image can accurately capture the aesthetic quality of the British landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Supported by the increasing availability of training data and high-performance computer hardware, deep learning has made automatic image classification and object detection tasks possible over large datasets, including social media 32 – 35 . As a result, deep learning has been identified as an important new tool in the development of rapid, flexible and transferable cultural ES indicators 36 .…”
Section: Introductionmentioning
confidence: 99%
“…We might say this evident fascination with mediated natures signifies a broader commitment to interpretative research, and thus a decisive move towards the social sciences and humanities in making sense of people–nature relations. This move is further evidenced by the maturing of work in the area of cultural ecosystem services, a recurring area of publication (Egarter Vigl et al, 2021; Gould et al, 2019; Jones et al, 2022) as well as the gradual treatment and application of concepts more familiar to critical theory researchers, among these discourse and metaphor analysis and the study of environmental aesthetics.…”
Section: Emerging Topics Themes and Emphasesmentioning
confidence: 99%
“…As Havinga et al (2020) demonstrate, geotagged social media are useful for measuring many types of CES including physical activity, aesthetic appreciation, ecological meaning, the development of knowledge and spiritual importance. Indeed, studies leveraging publicly available social media have begun investigating where environments provide aesthetically pleasing landscapes (Egarter Vigl et al, 2021; Figueroa‐Alfaro & Tang, 2017; Ghermandi et al, 2020), enjoyment of plants and animals (Richards & Friess, 2015), and opportunities to participate in religious (Roberts, 2017), spiritual (Oteros‐Rozas et al, 2018) or recreational activities (Väisänen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%